Aplikasi Prinsip-prinsip RIA dalam proses Formulasi Peraturan Daerah - Kristian Widya Wicaksono (Jurnal Administrasi Publik, 2008)
One of the implementations of good governance can be reflected in the capability of local government in making good regulations. In Public Administration science, such capability is often referred to as good regulatory governance. This means that people as taxpayers deserve quality service from local government, one of them is through local regulation  that benefits the people. It is because of this that we need to identify some effectives guidelines that could direct local government in issuing regulations.One of the guidelines is called Regulation Impact Assessment (RIA). RIA is a policy evaluation tool that would systemically assess the positive and negative influence of a particular policy being currently proposed (Asian Development Bank, 2003). RIA has several principles, among others are Principle of Neutrality in Competition, Principle of Effective Minimum Regulatory Needs, Principle of Participation and Transparancy, and Principle of Budget-Interest Effectiveness.Keywords: Governance, Regulation and Democracy